Impact of Civil Society and Government Organisations on Women Trafficking (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The aim of this study is to the Trafficking of women and children are not limited to territories ofa country. It extends well beyond the limits of any single country. Over time, various countries in SouthAsia have emerged as the most important nodal centres for trafficking sources, destinations, and transitsites. Commercial sexual exploitation and forced bonded labour are only two of the many objectives forwhich trafficking has become a major source, destination and transit point in India. The bulk of traffickingvictims are victims of intra-regional trafficking, although persons from countries like Nepal andBangladesh are also migrating across borders to be trafficked. The Middle East is also a destination for alarge number of trafficked Indian women and children who are subjected to forced labour bonds andcommercial sex exploitation. Underdeveloped places have a worse situation because of the push andpull factors that lead to trafficking and the balance between the mechanisms of demand and supply.Trafficking women and children from India's north-eastern states, as well as all of its neighbouringnations, despite several legal and constitutional remedies is still an ongoing problem. Women andchildren in this region have been particularly vulnerable to sexual exploitation as a result of extremistactivity, ethnic tensions, and disputes between various regional groups. The federal, state, and localgovernments, as well as non-governmental organisations (NGOs) working in this field, should take acomprehensive approach to combating human trafficking because of the problem's multifaceted nature.The condition of human trafficking around the world is being exacerbated by both Push and Pull causes.The most vulnerable people in society are those who are marginalized, backward, and socially andeconomically marginalized. Even more distressingly, among these trafficking victims, the female kidsuffers the most because she is regarded a nuisance or a burden rather than an asset by the family.